Odyssey Self Reflection - Gunpla / Faculty of Art and Design UiTM Cawangan Sarawak - Mohd Rathi, Mohd Razif (Perpustakaan Tun Abdul Razak, PTAR Universiti Teknologi Mara Cawangan Sarawak, 2021)
Wasted material from the “Gundam” model kit had inspired me to create the artworks that consisting of drawing, sculpture and painting. The concept of my artworks is from the futurism movement and transfer it to the “Gundam” model.